Influence of Electric Current and Hard Anodizing Process Time of Aluminium toward Hardness and Layer Thickness - Nitya Santhiarsa, I Gst. Ngr. (Jurnal Energi Dan Manufaktur; Vol 3, No.2 Oktober 2009)
Influence of Electric Current and Hard Anodizing Process Time of Aluminium toward Hardness and Layer Thickness
Keywords: Hard anodizing, electric current, immersion time